Stand Aerial Volume Tables for Miscellaneous Forests of Bastar - Joshi, S. C. (Indian Forester, 1973)
Ground and photo-measurements on 51 sample plots scattered over an area of 2182 hectares in West Bastar Forest Division were taken during February to June 1972. The ground plot-volume was calculated on the basis of diameter measurements of individual trees using P.I.S. local volume equations for various miscellaneous species. The ground-plot-volume was then correlated with the photo-plot measurements/estimates of plot-heights and density respectively. The analysis indicates that a significant correlation exists between the ground-plot-volume and the photo variables.